2022
DOI: 10.1002/lno.12264
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic, downstream‐propagating thermal vulnerability in a mountain stream network: Implications for biodiversity in the face of climate change

Abstract: As climate change continues to increase air temperature in high‐altitude ecosystems, it has become critical to understand the controls and scales of aquatic habitat vulnerability to warming. Here, we used a nested array of high‐frequency sensors, and advances in time‐series models, to examine spatiotemporal variation in thermal vulnerability in a model Sierra Nevada watershed. Stream thermal sensitivity to atmospheric warming fluctuated strongly over the year and peaked in spring and summer—when hot days threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
1
6
1
Order By: Relevance
“…We suspect that ponds are less sensitive to changes in air temperature because they are deeper, have higher thermal mass and volume-to-surface ratios, and are more connected to groundwater compared to creeks (MKWC 2014(MKWC , 2020(MKWC , 2022Wickman et al 2020). Other studies measuring thermal sensitivity to air temperature in snowmelt-fed streams in California's Sierra Nevada (Leathers et al 2022), or in highlatitude streams in Alaska (Lisi et al 2015), have generally reported higher thermal sensitivities than our study. Our measurements reflect an extreme drought period but still exhibited low thermal sensitivity compared to other published values.…”
Section: Off-channel Ponds Provide Diel and Seasonal Thermal Bufferingcontrasting
confidence: 77%
“…We suspect that ponds are less sensitive to changes in air temperature because they are deeper, have higher thermal mass and volume-to-surface ratios, and are more connected to groundwater compared to creeks (MKWC 2014(MKWC , 2020(MKWC , 2022Wickman et al 2020). Other studies measuring thermal sensitivity to air temperature in snowmelt-fed streams in California's Sierra Nevada (Leathers et al 2022), or in highlatitude streams in Alaska (Lisi et al 2015), have generally reported higher thermal sensitivities than our study. Our measurements reflect an extreme drought period but still exhibited low thermal sensitivity compared to other published values.…”
Section: Off-channel Ponds Provide Diel and Seasonal Thermal Bufferingcontrasting
confidence: 77%
“…To better understand the mechanisms controlling changes in secondary production across our study sites, we examined whether differences in invertebrate secondary production were better explained by differences in community composition (community turnover), or differences in production rates of shared taxa that occurred across sites. Our findings suggest that declining meltwaters may result in greater aquatic productivity, but-as previous studies have shown-this enhanced productivity is likely associated with the loss of distinct communities of organisms and more synchronized temporal dynamics of aquatic biodiversity (Hotaling et al 2019;Leathers et al 2023).…”
supporting
confidence: 56%
“…Although this study represents one of the most comprehensive comparative analyses of invertebrate community secondary production among streams reflecting different hydrochemical regimes (Birrell et al 2020; Leathers et al 2023), this level of detail reflects a trade off in single site‐level understanding vs. spatial replication over multiple representative streams. Interannual variation in secondary production is high in many streams, particularly in response to variation in discharge, ambient air temperatures, or marine‐derived nutrient subsidies from spawning salmon.…”
Section: Invertebrate Community Diversity Varies Among Stream Typesmentioning
confidence: 99%
“…It is a strength of this special issue to be representative of diverse habitats and scales, including alpine streams (Leathers et al 2023), wetlands of the North American Great Plains (Hu et al 2023), lakes (Hébert et al 2023; Katkov and Fussmann 2023; Su et al 2023), estuaries (Douglas et al 2023; Franzè et al 2023), tropical reefs (Lange et al 2023), and the arctic ocean (Ramondenc et al 2023), as well as diverse organisms, from single celled algal primary producers (Vrana et al 2023) to top consumers such as right whales (Meyer‐Gutbrod et al 2023). Moreover, contributions cover ecologically and climate‐relevant ranges of scales, including laboratory experimentation lasting days (Bomfim et al 2023; Carrier‐Bellau et al 2023, Fields et al 2023), mesocosm experiments of 1‐month duration (Katkov & Fussmann 2023; Wang et al 2023), as well as the paleorecord (Hu et al 2023).…”
Section: A Diverse Array Of Contributions With Common Themesmentioning
confidence: 99%
“…Several studies untangled the interactions between habitat complexity, interannual variability, and a myriad of other biotic and abiotic factors through time series analyses. Leathers et al (2023) studied the complex and scale‐dependent, land‐water connections that regulate water temperature change along high‐elevation stream networks, which support a diversity of thermally sensitive species. The cascading effects of upstream water warming were propagated downstream, and changed water and habitat quality.…”
Section: The Power Of Time Series Data and Analysismentioning
confidence: 99%